Udlandet tur-retur. Sådan får man også børn - Kroløkke, Charlotte Halmø (K&K - Kultur og Klasse, 2012)
GOING ABROAD AND BACK | How do Danish women negotiate egg donation when it involves travelling to clinics in Spain or the Czech Republic? This article employs anthropological and sociological feminist literature on assisted reproductive tech nologies and transnational reproduction to understand the dynamics at play when Danish women travel to Spain or the Czech Republic for egg donation. The empirical material includes interviews with Danish women who are either planning to travel or who have already travelled for egg donation. The essay suggests that Danish women employ conventional understandings of both femininity and nationalized discourses. They mediate their border crossings not only as a type of gifting but also as a particular type of transnational service. Fertility travel is naturalized, in these discourses in light of the interviewees’ desire to become mothers and, in the process, re-positioning transnational egg donation as a form of global sisterhood.